2016
DOI: 10.1016/j.jpsychires.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

History of childhood maltreatment augments dorsolateral prefrontal processing of emotional valence in PTSD

Abstract: Posttraumatic stress disorder (PTSD) is characterized by conflicting findings of both increased and decreased amygdala and prefrontal reactivity to threat or trauma stimuli. Childhood maltreatment (CM), a potent risk factor for PTSD, exerts long-lasting influences on threat processing and prefrontal-amygdala function. This suggests that CM history may influence PTSD neural phenotypes related to threat processing. Here, we adapt a well-characterized emotional conflict paradigm to investigate CM effects on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 33 publications
0
36
0
1
Order By: Relevance
“…Consistent with this regulatory hypothesis, work from our group using the current task in youth with PTSD revealed decreased amygdala-dmPFC coupling, which further related to illness severity (19). Furthermore, recent studies have demonstrated that, controlling for symptom severity, childhood maltreatment is associated with increased dorsolateral prefrontal activation in emotion tasks requiring cognitive control (9; 18), which may counteract re-experiencing symptoms (18) and amygdala hyperactivity (9). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this regulatory hypothesis, work from our group using the current task in youth with PTSD revealed decreased amygdala-dmPFC coupling, which further related to illness severity (19). Furthermore, recent studies have demonstrated that, controlling for symptom severity, childhood maltreatment is associated with increased dorsolateral prefrontal activation in emotion tasks requiring cognitive control (9; 18), which may counteract re-experiencing symptoms (18) and amygdala hyperactivity (9). …”
Section: Discussionmentioning
confidence: 99%
“…Together, these studies suggest that amygdala hyperactivation to negative stimuli may be an adaptive response to early life adversity, perhaps allowing enhanced threat detection. In contrast, prefrontal findings during emotion processing have been more variable and include mixed findings (increased and decreased activation) in the medial prefrontal cortex (mPFC) (5; 17), dorsolateral (dl)PFC (5; 7; 9; 18) and ventrolateral (vl)PFC (57; 17) in relation to interpersonal violence/maltreatment, caregiver deprivation, and poverty. Notably, abnormal prefrontal activation following early life adversity may also be specific to negative stimuli (6; 9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence to suggest that processing of emotional valence itself is altered in PTSD, in particular for individuals who have suffered childhood maltreatment 102103 . Given our desire to understand the basic neuroscience of negative emotions, there has been considerable recent effort made to use modern optogenetic and chemogenetic tools to understand the coding of valence in the mouse brain subpopulations of neurons in the BLA 104 , central amygdala 105 , nucleus accumbens 106 and ventral tegmental area (VTA) 107 , and other regions appear to respond to the appetitive or aversive qualities of a stimulus, independent of its sensory features 10 .…”
Section: Altered Cognition and Moodmentioning
confidence: 99%
“…On the other hand, we have proposed that enhanced coupling between the amygdala and more dorsal/lateral prefrontal regions involved in higher level appraisal and emotion regulation may reduce the likelihood of psychopathology following childhood trauma [45]. Supporting this notion, childhood trauma is actually associated with increased prefrontal recruitment and amygdala-prefrontal coupling during emotion regulation in otherwise healthy youth or when adjusting for affective symptoms [40,45,46,50,51]. Conversely, recent neuroimaging studies of pediatric PTSD suggest a failure to upregulate prefrontal circuits, but nevertheless show increasing amygdala reactivity with age.…”
Section: Impacts Of Child Trauma Exposure On Neurodevelopmentmentioning
confidence: 99%